When, how much, how fast, and why it matters; a quantitative view of stratigraphy and the emergence of a new paradigm - Lunt, Peter; Luan, Xiwu (Berita Sedimentologi, 2024)
Our understanding of the regional geology of SE Asia appears to have stagnated and, to break out of this state, a new approach to stratigraphic studies is required. We must avoid the trap of deductive studies and boilerplate formats as these restrictive methods of investigation rely heavily on assumptions that are not valid in the tectonically active basins of the region. This review examines an alternative workflow that replaces model-based methods with evidence-based ones, and in particular uses stratigraphic properties in a quantitative way to test old concepts. Through this approach a tectono-stratigraphic framework is established, and new data is used to test and then build upon this interdisciplinary framework. It is argued that only this approach can accommodate and predict the unique and locally complex geology of the region. A key component of this approach is the now stable, cross-facies, biostratigraphy, and time scale for the later Eocene to Recent of SE Asia, as well as methods in estimating paleo-bathymetry. These can be used to evaluate the sedimentary history and structural evolution of the basins, using geohistorical analysis.The application of this quantitative approach, combined with a more open attitude to sub-surface data from government authorities, makes it highly probable that there will be a paradigm shift in our understanding of regional geology across SE Asia. Examples given here illustrate the use of the quantitative methods in rejecting long-established and widely cited old ideas, and the start of building of new concepts. We have not yet arrived at the new paradigm, but we can already observe that the attenuation of Sundaland, with two separate axes of extension, both with simultaneous episodes of movement, is not consistent with any current plate tectonic hypothesis, or even any known plate mechanism. The new framework is argued to be both innovative and predictive, replacing the largely descriptive and enervated role of geology in the past few decades. A new, evidence-based role will offer a better understanding of facies palaeogeography through time and exploration risks.